Remodelling and Improvements in Organoid Technology to Study Liver Carcinogenesis in a Dish - Umesh Tharehalli; Michael Svinarenko; André Lechel (Hindawi Limited, 2019)
Primary liver cancer (PLC) is the sixth most common tumour disease and one of the leading causes of cancer-related death worldwide. The two most common types of PLC are hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (iCCA). Diverse subgroups are described and a manifold number of gene mutations are known. Asymptomatic disease progression and limited therapeutic options are the reasons for the high mortality rate in PLC. Up to date, the multikinase inhibitors sorafenib and lenvatinib are the only FDA-approved first-line treatments for advanced HCC. One of the major drawbacks in the preclinical drug development is the lack of suitable model systems. In recent years, 3D organoid cultures were established from several organs and tumour subtypes, thereby opening new avenues in tumour research. 3D organoid cultures are used to describe the tumour diversity, for cancer modelling in a dish and for therapy responsiveness. The establishment of living biobanks and the development of next-generation matrices are promising approaches to overcome drug resistance and to improve the quality of personalised anticancer strategies for patients with PLC. In this review, we summarise the current knowledge of 3D cultures generated from healthy liver and primary liver cancer.